Project Delays and Project Property Investment Decisions in Apartments: A Literature Review - Oktaviastuti, Blima; Leliana, Arinda; Arifin, Isnani (Universitas Tribhuwana Tunggadewi Malang, 2023)
Apartment housing has become an option in big city areas, especially as land is becoming increasingly scarce and expensive. Apartment investment is an investor's choice at a time when demand is increasing every year along with the growth of the urban economy. Apartment construction projects begin construction based on appropriate planning to produce buildings of the right quality, cost, and time by minimizing one aspect of risk, namely the project delay factor. This article aims to present studies related to construction project delay factors; apartment buildings; investment analysis; and the impact of project delays on investment interest. The results show that construction delays have an impact on construction costs and time and further research is needed on the effects on investors' investment interest.ABSTRAKHunian apartemen menjadi salah satu pilihan di Kawasan kota besar terlebih lahan yang semakin berkurang dan mahal. Investasi apartemen menjadi pilihan investor di kala kebutuhan yang semakin tinggi tiap tahunnya seiring bertumbuhnya perekonomian di perkotaan. Proyek konstruksi apartemen memulai pembangunan yang didasarkan pada perencanaan tepat guna untuk menghasilkan bangunan yang tepat mutu, biaya dan waktu dengan meminimalkan salah satu aspek risiko yaitu faktor keterlambatan proyek. Artikel ini bertujuan memaparkan kajian terkait: faktor keterlambatan proyek konstruksi; bangunan apartemen; analisa investasi; dampak keterlambatan proyek terhadap minat investasi. Hasil didapatkan bahwa keterlambatan konstruksi berdampak terhadap biaya dan waktu konstruksi dan diperlukan penelitian lebih lanjut efek terhadap minat investasi investor.